The Effect of Brilliant Blue-Based Plaque-Staining Agents on Aesthetic Orthodontic Appliances - Justyna Topolska (MDPI AG, 2021)
Orthodontic appliances discolour over treatment time, and a yellowish plaque builds up on the contact area of the brackets, adhesive and teeth. Brilliant Blue-based plaque-staining agents (BBPSAs), which increase tooth brushing efficiency, have the potential to support the maintenance of proper oral hygiene during orthodontic treatment. However, they exhibit strong colouring properties, and their impact on the aesthetics of braces remains unclear. Therefore, the aim of this study was to investigate the influence of commercially available BBPSAs on the colour of aesthetic orthodontic materials. A light-cured, colour-changing orthodontic adhesive and new-generation, monocrystalline, sapphire brackets were chosen for the experiments. The effect of the staining agent on the tested materials was investigated in terms of the reaction temperature and time, as well as the presence of black tea-induced impurities on the materials. The CIELAB (Commission Internationale de L’éclairage L* a* b*) colour system parameters were measured, and the colour differences (ΔE*ab and ΔE00—the Commission Internationale de L’éclairage 2000 colour-difference) were determined for the materials under several experimental conditions. The braces’ green-red colour expression was positively affected by the BBPSA. Under in vitro conditions, the regular use of the BBPSA for 90 days visibly improved the unfavourable colour change caused by the black tea.